Finance and Development, March 2018. (Finance and Development; Finance and Development ;, 2018)
This issue focuses on recent experiences that holds lessons for when to tackle debt and when not to. Growth is picking up, and the IMF has been ratcheting up its forecasts. Government coffers are filling and, with more people at work, demand for public social support is receding. Research shows that the stimulatory effect of fiscal expansion is weak when the economy is close to capacity. Low-income economies may be at greatest risk. Traditionally, they borrowed from official creditors at below-market rates. Higher global rates could divert precious budget resources to debt servicing from crucial infrastructure projects and social services. Raising budget balances toward their medium-term targets can be achieved at little cost to economic activity. Growth-enhancing infrastructure investments and crucial social services such as health and education should be maintained. Well-designed fiscal policy can address inequality and stimulate growth.